(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the role of Diffusion-weighted magnetic resonance imaging and apparent diffusion coefficient (ADC) values in the differential diagnosis of solid lesions of the breast. Materials and Methods: Diffusion-weighted images and ADC values from 36 women with 37 solid lesions definitely diagnosed through breast biopsy and post-surgical histopathology were evaluated retrospectively. ADC values obtained from malignant and benign solid lesions of the breast were compared using the t-test. The optimum threshold value for use in differentiating benign and malignant lesions was determined using ROC analysis, and sensitivity and specificity values were calculated.Results: Histological analysis identified 23 lesions and 14 benign lesions. Mean age (49 ± 7.8 years) was higher in the group with malignant breast lesions than in the group with benign breast lesions (37.3 ± 8.2) (p 0.05). The mean ADC value (1.1 ± 0.2 × 10-3 mm2/s) in the patients with malignant breast lesions was significantly lower than in the group with benign breast lesions (1.49 ± 0.18 × 10-3 mm2/s) (p 0.05). When the threshold value to be used in the ROC curve was applied the differentiation of benign and malignant solid lesions, the sensitivity was 78.3% and specificity was 100%.Conclusions: Diffusion-weighted MRI and ADC values have the potential to contribute to the diagnosis of solid lesions in the breast at conventional MR examination by differentiating between benign and malignant tumors.